6.2k views
1 vote
solve the following system of equation using the substitution method 5x + 3y equals 1 x + 2y equals 3

solve the following system of equation using the substitution method 5x + 3y equals-example-1

1 Answer

2 votes

5x + 3y = 1 Equation (1)

x + 2y= 3 Equation (2)

Isolating x in the equation 2, we have:

x = 3 - 2y

Replacing x=3- 2y in the equation 1, we have:

5(3 - 2y) + 3y = 1

15 -10y + 3y = 1 (Distributing)

15 -7y = 1 (Adding like terms)

-7y = 1 - 15 (Subtracting 15 on both sides of the equation)

-7y = -14 (Subtracting)

y= -14/(-7) (Dividing by - 7 on both sides of the equation)

y = 2

Replacing y=2 in the equation 2

x = 3 - 2*2

x= 3 - 4 (Multiplying)

x= -1 (Subtracting)

The answers are : x= -1 and y=2.

User Jonas Tundo
by
4.6k points